Extent of adoption of improved fish farming practices by the farmers in North-eastern region of India - Singha, A. K.; Tripathi, A. K.; Jat, P. C.; Bordoloi, R.; Sinha, J. K. (Indian Journal of Fisheries, 2017)
This study, to analyse the extent of adoption of improved fish farming practices by the farmers, was conducted in 13 purposively selected districts having Krishi Vigyan Kendras (KVKs) in the north-eastern region of India with 130 samples each from KVK adopted and non-adopted villages respectively through proportionate random sampling technique. Data from selected respondents were collected with the help of pre-tested structured schedule through personal interview method. The study revealed that majority of the respondents in KVK adopted villages had medium level of adoption of improved fish farming practices, while over half of the total respondents in non-adopted villages showed poor adoption level of the same fish farming practices. Specific practices like recommended size of ponds for pond management, bottom raking for pond preparation and maintenance of adequate dissolved oxygen concentrations in ponds to prevent fish stress were found to have little/no adoption among both categories of respondents.